Jewels of stringology: text algorithms - Crochemore, Maxime; Rytter, Wojciech (World Scientific Publishing Co. Pte. Ltd, 2002)
This work deals with the basic algorithms in the area of stringology. It reflects the relationships between applications of text-algorithmic techniques and the classification of algorithms according to the measures of complexity considered.